Farmer’s Perceptions of the Upland Garlic Program in East Lombok Regency Through Sustainable Cultivation Practice - Channy Rosalia Gemala Hati Nainggolan; Soemarno; Fitri Candra Wardana (The Journal of Indonesia Sustainable Development Planning, 2025)
East Lombok Regency is the second largest garlic center in Indonesia, receiving special attention from the government to increase farmer productivity and income through the Upland Garlic program, which has been running for 5 years. Therefore, this study aims to analyze the level of farmer satisfaction with the performance of the Upland Garlic program in East Lombok Regency. This research was conducted from April to June 2025 by distributing 68 questionnaires consisting of 34 question indicators and 4 dimensions (Input, Process, Output, and Outcome) to randomly selected farmer group leaders. The data was then analyzed using Service Quality (SERVQUAL) and Customer Satisfaction Index (CSI). The analysis of the 34 indicators showed that 19 indicators had a negative gap value, meaning that the program's performance did not meet farmer’s expectations, while 15 indicators had a positive gap value, meaning that the program's performance met farmer’s expectations. Overall, farmers were very satisfied with the Upland Garlic program, with a CSI value of 79.66%.